1987
DOI: 10.2514/3.45407
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws for testing airfoils under heavy rainfall

Abstract: Subscale test data have shown that airfoils operating in a simulated heavy-rain environment can experience significant performance penalties. The physical mechanism resulting in this performance penalty has yet to be conclusively identified. Therefore, the extrapolation of subscale data to full-scale conditions must be undertaken with extreme caution since complete scaling laws are unknown. This paper discusses some of the technical issues that must be addressed and resolved prior to extrapolating the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In wind tunnel experiments or numerical simulations, the scaled models of aerofoils and wings are usually adopted for our analysis of rain effects. In 1987, Bilanin (22) addressed the subject of scaling laws for model tests of aerofoils in simulated rain and determined that variables such as kinematic viscosity, surface tension interaction, mean raindrop spacing, air and raindrop density, volumetric mean droplet diameter and drop velocity are necessary parameters for scaling rain effects on aerofoil aerodynamic performance. As scaled rain model is used in our simulation, scaling laws are implemented given by:…”
Section: Modelling Of Rainmentioning
confidence: 99%
See 1 more Smart Citation
“…In wind tunnel experiments or numerical simulations, the scaled models of aerofoils and wings are usually adopted for our analysis of rain effects. In 1987, Bilanin (22) addressed the subject of scaling laws for model tests of aerofoils in simulated rain and determined that variables such as kinematic viscosity, surface tension interaction, mean raindrop spacing, air and raindrop density, volumetric mean droplet diameter and drop velocity are necessary parameters for scaling rain effects on aerofoil aerodynamic performance. As scaled rain model is used in our simulation, scaling laws are implemented given by:…”
Section: Modelling Of Rainmentioning
confidence: 99%
“…It is assumed that the rain droplets in present study are non-evaporating, non-interacting and non-deforming spheres. The former assumption of non-interacting droplets has been justified by Bilanin (22) . According to his study even for high rainfall of 1,872mm/h and for an average raindrop diameter of 4mm, the mean distance between raindrops will be of the order of 70mm or 17•5 times the droplet diameter.…”
Section: Introductionmentioning
confidence: 99%
“…and it represents the probability of finding drops of diameter in a sample of splashed raindrops. Bilanin [28] has investigated the evaporation of the particles near the surface and found that evaporation does not affect the airfoil aerodynamic efficiency, so in our study we ignore the vaporization of water film. Since the film particle vaporization is ignored, only the momentum and energy conservation equations remain in the conservation equations for wall-film particles.…”
Section: Wall-film Modelmentioning
confidence: 99%
“…We assume that the rain particles are noninteracting. Bilanin [30] showed in his study that, even for extremely high rainfall of 1872 mm∕h, for an average raindrop diameter of 4 mm, the mean distance between raindrops should not be less than 70 mm or 17.5 times the drop diameter. Therefore, raindrop collisions cannot occur frequently enough, and we can neglect the collisions of the particles in our rain model.…”
Section: Introductionmentioning
confidence: 99%